Das Personal in der Weiterbildung Arbeits- und Beschäftigungsbedingungen, Qualifikationen, Einstellungen zu Arbeit und Beruf - wb-Personalmonitor, Autorengruppe (W. Bertelsmann Verlag, 2016)
Who is employed in further education programmes? What are their qualifications? Under which conditions do they work and how satisfied are they with their work? It is the first study to provide representative data on the qualifications, employment situations and working conditions of employees in the adult and further education industry. The data of this two-step personnel survey was collected in 2014. More than 6,000 adult educators from more than 1,800 training institutions participated in the survey. This study serves as a supplement to educational reporting in Germany, which has hitherto rather been focussed on providers, offers and participation. Furthermore, it offers a reliable basis for assessments regarding the professionalisation of adult and further education. Moreover, the collected data may be used for further research.
Description based on print version record.
KU Open Services
Keywords: Social Science / Sociology; Social sciences; Electronic books